Explosion in the species number of Phytophthora genus and its influences on ecology and economy - Érsek, Tibor (Acta Agraria Debreceniensis, 2014)
This short abstract and the presentation summarize the latest changes in taxonomy and ecology of Phytophthora species. Occurrence of new P. species in the region have economy impacts as well.